PHILOSOPHY, HUMANISM AND DEVELOPMENT IN AFRICA: FURTHER REFLECTIONS ON HENRY ODERA ORUKA - oni, Adetunji; Fayemi, Kazeem (Al-Adab Journal, 2025)
Since the wake of postcolonial era in Africa, philosophers have unceasingly reflected on political ideas that can serve as harbinger for social transformation and development in Africa; from socialism, Marxism, welfarism, Pan-Africanism, Ubuntuism, to humanism. Odera Oruka is one of the foremost African philosophers whose thoughts on humanism and philosophy, though less known and controverted, entail some strategic directions for addressing the challenges of development in Africa. This paper seeks to interrogate Oruka’s understanding of humanism and philosophy in Africa in order to explore its functional relation to the question of development. Oruka conceives humanism as the ultimate moral standard, which involves the quality and security of human life. Bemoaning the obscene disregard for humanism in Africa, Oruka hypothesizes a critical and dialectical philosophy as an antidote to what he called ARID (African Republic of Inhumanity and Death). Notwithstanding the fertile points in Oruka’s thought, arguments are raised in this paper that humanism is a concept with diverse interpretations, which apparently do not fit into one formula as Oruka depicts. Beyond Oruka’s discourse on philosophy and humanism in Africa (as opposed to African philosophy and African humanism), this paper discusses the view that sees African humanism as the defining element of the Africaness of African philosophy. It consequently defends the position that African humanism can serve as a positive ideological springboard for sustainable development in Africa.